79.5k views
3 votes
Help me find the answer

Help me find the answer-example-1
User Systemboot
by
5.3k points

2 Answers

4 votes
I think it would be 20.
H(n-2) times h(n-1)=
H(3-2) times h(3-1)=
H(1) times h(2) which we are told are...
-10(-2)=20
User Eric Ness
by
4.9k points
2 votes

Answer:

38.5

Explanation:

Lets say, first number = x



Second number = 3x+7



Total = 49




(x)+(3x+7)= 49



4x+7 = 49



4x = 42



x = 42/4



x= 10.5




x= 10.5



3x+7 = 3(10.5)+7 = 38.5




Hope this helps!!

User Jgauffin
by
4.7k points